Catalyst for preparing styrene through ethylbenzene dehydrogenation as well as preparation method and application of catalyst
Through the combination of Fe2O3, K2O, CeO2, MoO3, TiO2, MnO2, Co3O4 catalysts and the regulation of the exposed crystal surface area of TiO2 (001), the problem of insufficient activity and stability of ethylbenzene dehydrogenation is solved, and high activity is achieved , selectivity and stability meet the styrene production needs for industrial applications.
Patent Information
- Application Number
- CN202310819173.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-05
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2043-07-05
AI Technical Summary
The existing ethylbenzene dehydrogenation catalysts are not very active, have poor stability and have low styrene selectivity, which cannot meet the needs of industrial applications.
The catalyst composed of Fe2O3, K2O, CeO2, MoO3, TiO2, MnO2, Co3O4 is used to regulate the exposed crystal surface area of TiO2 (001) and combine the synergistic effect of Fe-K-Ce-Mo-Mn-Co-based catalyst to improve the catalyst's Activity and selectivity.
It significantly improves the activity, selectivity and stability of the catalyst, reduces the production of by-products and carbon deposits, improves the conversion rate of ethylbenzene and styrene yields, and meets the needs of industrial applications.
Smart Images

Figure CN119259016A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a catalyst for preparing styrene by dehydrogenating ethylbenzene, a preparation method and application thereof, and belongs to the technical field of dehydrogenation catalysis in chemical catalysis. Background Art
[0002] Styrene is an important basic organic raw material, mainly used to manufacture polystyrene resin, unsaturated polyester resin, ion exchange resin, synthetic resin coating and insulator and other materials. These materials have very important uses in industrial sectors such as automobile manufacturing, household appliances, textiles, building materials, light industry, toys, etc. So far, the catalytic dehydrogenation of ethylbenzene has always been the main technical route for producing styrene, and its production capacity accounts for about 85% of the total production capacity of styrene. The most important core technology in this method is the research and development of high-performance ethylbenzene dehydrogenation catalyst for styrene. In current industrial applications, the catalyst for ethylbenzene dehydrogenation to styrene is usually a Fe-based oxide and a promoter doped with potassium. CN103769141B discloses a synthetic preparation method of such Fe-K-based oxide catalyst.
[0003] In the catalytic dehydrogenation of ethylbenzene, toluene and benzene are the main by-products. The by-product benzene can be separated by a distillation unit and then returned to the ethylbenzene unit for recycling, while the toluene with low economic value can only be sold as a low-priced by-product. While increasing the ethylbenzene conversion rate and reducing the amount of by-products generated can improve the utilization rate of the raw material ethylbenzene, reduce the material consumption of the device, and increase economic benefits. Styrene devices preferably use catalysts with high catalytic activity and good styrene selectivity. The currently disclosed ethylbenzene dehydrogenation catalysts for styrene production mainly use methods such as improving the catalyst structure stability and modifying the catalyst surface properties to improve the catalyst activity, selectivity and stability under reaction conditions. CN108097260B discloses a K2Fe 10 O 16 -K2O-CeO2-WO3-based catalyst, by introducing at least one alkali metal oxide of Rb2O and Cs2O, the surface of potassium ferrate oxide is modified to improve the catalytic activity and stability of the catalyst in the dehydrogenation of ethylbenzene to produce styrene, and achieve high styrene yield and styrene selectivity under low water ratio conditions. CN101829576B discloses a preparation method in which a catalyst based on Fe2O3-K2O-Ce2O3-MoO3 is added with CaO, BaO, CuO, ZnO2, Co2O3, La2O3 and various metal oxides as stabilizing agents. The obtained catalyst has high activity and selectivity, low deactivation rate and high stability in the dehydrogenation reaction of ethylbenzene. However, the benefits of the method so far are not obvious, and the catalytic activity and styrene selectivity of the catalyst cannot fully meet the needs of the practical application of the catalyst for dehydrogenation of ethylbenzene to produce styrene. Summary of the invention
[0004] In view of the problems of low activity, poor stability and low styrene selectivity of ethylbenzene dehydrogenation catalyst in the prior art, the present invention provides a ethylbenzene dehydrogenation styrene catalyst and its preparation method and application. The catalyst is applied to the ethylbenzene dehydrogenation styrene reaction and has the characteristics of high catalytic activity, good catalyst stability and high styrene selectivity. The preparation method has the characteristics of simple process flow.
[0005] The first aspect of the present invention provides a catalyst for the dehydrogenation of ethylbenzene to produce styrene. The catalyst comprises Fe2O3, K2O, CeO2, MoO3, TiO2, MnO2, and Co3O4, wherein the exposed crystal surface area of TiO2 (001) accounts for more than 60% of the total exposed crystal surface area of TiO2.
[0006] According to the present invention, preferably, the exposed crystal surface area of TiO2 (001) in the catalyst accounts for more than 67% of the total exposed crystal surface area of TiO2, preferably 67% to 98%, for example but not limited to 69%, 71%, 73%, 78%, 80%, 83%, 87%, 91%, 94%, 98% and the like.
[0007] According to the present invention, the catalyst, based on the total mass of the catalyst and calculated by mass fraction, comprises the following components:
[0008] (a) 58% to 76% Fe2O3;
[0009] (b) 6% to 12% K2O;
[0010] (c) 5% to 10% CeO2;
[0011] (d) 3% to 7.5% MoO3;
[0012] (e) 4% to 8.5% TiO2;
[0013] (f) 1.8% to 5.4% MnO2;
[0014] (g) 0.6% to 1.8% Co3O4.
[0015] The second aspect of the present invention provides a method for preparing a catalyst for dehydrogenating ethylbenzene to produce styrene. The method comprises:
[0016] (1) A Ti source, hydrofluoric acid and a base M are uniformly mixed and then calcined for the first time; the base M comprises at least one selected from ammonia water and a quaternary ammonium base.
[0017] (2) The calcined product of step (1) is uniformly mixed with Fe source, K source, Ce source, Mo source, Mn source and Co source, molded and calcined for the second time to obtain the catalyst.
[0018] According to the present invention, in the method, the reaction device in step (1) is an autoclave, preferably an autoclave lined with polytetrafluoroethylene. The pressure in step (1) is autogenous pressure. The mixing in step (1) is mechanical stirring; the stirring time is 20 to 40 minutes; further, after the materials in step (1) are evenly mixed, they are heated. The heating temperature is 180 to 200°C and the time is 18 to 26 hours. After heating, it is cooled naturally, and preferably the cooling rate is 5 to 10°C / min. After cooling, it can be optionally centrifuged, optionally washed, and optionally dried before the first roasting. Water and / or anhydrous ethanol can be used for washing. The drying conditions are: drying at 80 to 100°C for 10 to 12 hours.
[0019] According to the present invention, in the method, the conditions of the first calcination in step (1) are: the calcination temperature is 550-800°C, preferably 600-750°C; the calcination time is 3-5h, preferably 1.5-3.5h. The heating rate during the heating process during calcination is 1-5°C / min. The calcination atmosphere is an oxygen-containing atmosphere, preferably air. The first calcination product is a TiO2 solid.
[0020] According to the present invention, in the method, the Ti source in step (1) includes at least one of tetrabutyl titanate, tetraisopropyl titanate, titanium tetrachloride and titanium sulfate, preferably tetrabutyl titanate and / or tetraisopropyl titanate.
[0021] According to the present invention, in the method, in step (1), the quaternary ammonium base includes at least one selected from tetramethylammonium hydroxide, tetraethylammonium hydroxide, and tetrapropylammonium hydroxide, preferably at least one selected from tetrapropylammonium hydroxide and tetraethylammonium hydroxide.
[0022] According to the present invention, in the method, in step (1), the mass concentration of aqueous ammonia is 22-28%.
[0023] According to the present invention, in the method, in step (1), the mass concentration of the hydrofluoric acid is 38-44%.
[0024] According to the present invention, in the method, in step (1), the mass ratio of hydrofluoric acid, base M, and Ti source is 1:0.17-3.13:12.4-16.5, preferably 1:0.45-2.6:13.05-15.63; wherein hydrofluoric acid is calculated as HF, base M is calculated as base M itself, and Ti source is calculated as Ti source itself. When base M is ammonia water, it is calculated as NH3·H2O. When base M is a quaternary ammonium base, it is calculated as tetramethylammonium hydroxide, tetraethylammonium hydroxide and / or tetrapropylammonium hydroxide.
[0025] According to the present invention, in the method, in step (2), the molding is kneading molding, preferably extrusion molding. The extrusion molding method forms integral regular catalyst particles with a diameter of 2 to 5 mm and a length of 3 to 10 mm. Water can be added or evaporated as needed during the molding process. Preferably, the amount of water added accounts for 15 to 25% of the total amount of raw materials. After kneading molding, it can be dried at a drying temperature of 60 to 180°C; and / or, the drying time is 8 to 20 hours.
[0026] According to the present invention, in the method, in step (2), the conditions for the second calcination are: calcination temperature of 600-900°C; calcination time of 3-7h; heating rate of 10-15°C / min.
[0027] According to the present invention, in the method, in step (2), the mixing method can be a conventional mechanical stirring method.
[0028] According to the present invention, in the method, in step (2), the Fe source, K source, Ce source, Mo source, Mn source, and Co source are oxides and / or salts. Preferably, the Fe source includes one or more of ferric oxide, ferric chloride, ferric acetate, ferric nitrate, and ferric sulfate; and / or, the K source includes one or more of potassium carbonate, potassium bicarbonate, potassium nitrate, potassium chloride, and potassium sulfate; and / or, the Ce source includes one or more of cerium carbonate, cerium oxalate, cerium nitrate, cerium acetate, cerium chloride, and cerium sulfate; and / or, the Mo source includes one or more of ammonium molybdate and ammonium phosphomolybdate; and / or, the Mn source includes one or more of manganese dioxide, manganese chloride, manganese acetate, manganese nitrate, and manganese sulfate; and / or, the Co source includes one or more of cobalt nitrate, cobalt acetate, cobalt chloride, cobalt sulfate, and cobalt acetylacetonate.
[0029] According to the present invention, in the method, in step (2), the catalyst comprises Fe2O3, K2O, CeO2, MoO3, TiO2, MnO2, Co3O4, wherein the exposed crystal surface area of TiO2 (001) accounts for more than 60% of the total exposed crystal surface area of TiO2, preferably 60% to 98%. Preferably, the exposed crystal surface area of TiO2 (001) in the catalyst accounts for more than 67% of the total exposed crystal surface area of TiO2, further preferably 67% to 98%, for example but not limited to 69%, 73%, 78%, 80%, 83%, 87%, 91%, 94%, 98%, etc.
[0030] According to the present invention, in the method, in step (2), the catalyst, based on the total mass of the catalyst and calculated by mass fraction, comprises the following components:
[0031] (a) 58% to 76% Fe2O3;
[0032] (b) 6% to 12% K2O;
[0033] (c) 5% to 10% CeO2;
[0034] (d) 3% to 7.5% MoO3;
[0035] (e) 4% to 8.5% TiO2;
[0036] (f) 1.8% to 5.4% MnO2;
[0037] (g) 0.6% to 1.8% Co3O4.
[0038] The third aspect of the present invention provides the use of the above ethylbenzene dehydrogenation catalyst or the catalyst prepared by the above preparation method in the reaction of dehydrogenating ethylbenzene to produce styrene.
[0039] According to the present invention, the application uses ethylbenzene as a raw material, and the raw material is contacted with an ethylbenzene dehydrogenation catalyst to react to obtain styrene.
[0040] According to the present invention, the application conditions are: the reaction pressure is 20-100 kPa (absolute pressure); the mass space velocity of ethylbenzene is 0.2-2.0 h -1 ; The reaction temperature is 580-640°C; The water ratio (wt) is 1.0-2.0.
[0041] Compared with the prior art, the present invention has the following advantages:
[0042] (1) In the prior art, the effect of the exposed crystal face of TiO2 on the catalyst performance in the reaction of ethylbenzene dehydrogenation to styrene has not been studied. The inventors have found through research that in the reaction of ethylbenzene dehydrogenation to styrene, the catalytic performance of the catalyst can be directly affected by regulating the exposed crystal face of TiO2 in the catalyst. In the catalyst of the present invention, when the exposed crystal face area of TiO2 (001) is controlled to account for more than 60% of the total exposed crystal face area of TiO2, the TiO2 nanosheets mainly exposed (001) crystal face cooperate and synergize with the Fe-K-Ce-Mo-Mn-Co-based catalyst, which can significantly improve the activity, selectivity and stability of the catalyst. When the proportion of the exposed (001) crystal face of TiO2 exceeds 60%, preferably more than 67%, the migration ability of the active species on the catalyst surface will be significantly enhanced, thereby reducing the generation of by-products and carbon deposits, thereby improving the selectivity of the catalyst.
[0043] (2) In the preparation method of the catalyst of the present invention, a TiO2 precursor is first prepared, and then mixed with other metal sources and shaped and calcined to obtain the catalyst. At the same time, in the method, during the preparation of the TiO2 precursor, by adjusting the relative addition amounts of the titanium source, hydrofluoric acid, and base M, the surface structure of TiO2 in the catalyst can be well adjusted, so that the proportion of the exposed crystal face of TiO2 (001) exceeds 60%, preferably more than 67%. The catalyst prepared by this method is conducive to improving the adsorption of the reactants, especially ethylbenzene molecules on the catalyst, thereby improving the catalytic activity.
[0044] (3) In the application of the catalyst of the present invention, the catalyst is used in the dehydrogenation of ethylbenzene to produce styrene, and has the characteristics of high catalytic activity, good selectivity, good stability and simple preparation process. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 This is a photograph of the main exposed crystal planes of the catalyst obtained in Example 1 of the present invention measured by HR-TEM.
[0046] Figure 2 This is a photograph of the main exposed crystal planes of the catalyst obtained in Comparative Example 1 of the present invention tested by HR-TEM.
[0047] Figure 3 This is the in-situ infrared ethylbenzene transient reaction characterization result of the catalyst obtained in Example 1 of the present invention.
[0048] Figure 4 This is the in-situ infrared ethylbenzene transient reaction characterization result of the catalyst obtained in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0049] In order to more clearly explain the present invention, the following embodiments are given, but the present invention can be implemented in a manner not limited to the scope of the embodiments.
[0050] In the present invention, the activity of the catalyst is evaluated in an isothermal fixed bed. For the activity evaluation of the catalyst for dehydrogenation of ethylbenzene to produce styrene, the process is briefly described as follows:
[0051] Deionized water and ethylbenzene are respectively fed into the preheating mixer through metering pumps, and then preheated and mixed into gaseous state before entering the reactor. The reactor is heated by electric heating wire to reach the set temperature. The reactor is a stainless steel tube with 100 mL of catalyst filled inside. The reactants flowing out of the reactor are condensed with water and analyzed for their composition by gas chromatography.
[0052] The ethylbenzene conversion rate and styrene selectivity are calculated according to the following formula:
[0053]
[0054]
[0055] In the present invention, the HR-TEM test of the exposed crystal plane adopts the TitanCubed Themis G2 300 transmission electron microscope corrected by FEI Company. The ratio of the TiO2 (001) crystal plane to the total exposed crystal plane of TiO2 is obtained by statistics and calculation based on the HR-TEM morphology photos and geometric structure characteristics of the catalyst sample, that is, the ratio of the observed TiO2 (001) crystal plane to the total exposed crystal plane of TiO2. The total exposed crystal plane of TiO2 is the sum of the exposed crystal planes of TiO2 (001) and TiO2 (101).
[0056] In the present invention, the in situ DRIFTs characterization test instrument is a Nicolet IS50 infrared spectrometer from ThermoFisher. The in situ reaction cell uses a Harrick Scientific infrared reaction cell equipped with a mercury-cadmium-telluride MCT / A detector. The spectrum acquisition range is 1500-900cm -1 , resolution 4cm -1 (The number of scans was 64 times). All collected spectra used Kubelka-Munk intensity units. The loading amount of the catalyst in the in-situ pool was 0.8 mL, the ethylbenzene reaction gas was a mixed gas of 1000 ppm (volume concentration, carrier gas was N2), and the test flow rate was 20 mL / min. During the test, each catalyst was pretreated at 300°C for 30 minutes under a high-purity N2 atmosphere, and then the background spectrum was collected at 620°C. The infrared spectra collected in the transient reaction experiment were all deducted from the background spectrum of the corresponding temperature collected in advance. The reaction temperature was maintained at 620°C, the reaction gas was introduced, and the changes in the surface reaction of each catalyst over time were observed (within 30 minutes). The maximum value of the Kubelka-Munk intensity of the ethylbenzene adsorption vibration peak is the maximum value within the 30-minute reaction time. The larger the maximum value of the Kubelka-Munk intensity of the ethylbenzene adsorption vibration peak, the better the adsorption of the catalyst to the ethylbenzene molecule, thereby improving the catalytic activity. In the present invention, in the in-situ infrared spectrum of the catalyst, the maximum value of the Kubelka-Munk intensity of the ethylbenzene adsorption vibration peak is greater than 0.47.
[0057] In the present invention, the evaluation results of the catalysts of various examples are shown in Tables 1 and 2.
[0058] Example 1
[0059] (1) According to the mass ratio of hydrofluoric acid, alkali M, and Ti source of 1:0.78:13.48, tetrabutyl titanate, 40wt% hydrofluoric acid, and tetrapropylammonium hydroxide were weighed and mixed, stirred for 30 minutes, and then placed in an autoclave with a polytetrafluoroethylene liner and kept at 180°C for 24 hours. After the autoclave was naturally cooled (natural cooling rate was 5°C / min), the product was centrifuged, washed with deionized water and anhydrous ethanol, and dried at 80°C for 12 hours. Then it was calcined at 650°C for 2 hours to obtain TiO2 solid.
[0060] (2) In parts by weight, weigh 68 parts of ferric oxide equivalent to Fe2O3, 8.5 parts of potassium carbonate equivalent to K2O, 7.2 parts of cerium nitrate equivalent to CeO2, 5.3 parts of ammonium molybdate equivalent to MoO3, 3.6 parts of manganese nitrate equivalent to MnO2, 1.2 parts of cobalt acetate equivalent to Co3O4 and 6.2 parts of titanium dioxide solid obtained in step (1) equivalent to TiO2, stir in a mixing container for 2 hours until the mixture is uniformly mixed and add an appropriate amount of water. The amount of water added is 21wt% of the total amount of raw materials.
[0061] Then, the pellets were extruded and pelletized to obtain pellets with a diameter of 3 mm and a length of 5 mm, which were placed in an oven and dried at 80°C for 4 hours and 150°C for 10 hours. Then, the pellets were placed in a muffle furnace and calcined at 800°C for 5 hours to obtain a monolithic regular finished catalyst. The heating rate during the calcination process was 10°C / min.
[0062] The main exposed crystal surface photos of the catalyst obtained in this example are shown in HR-TEM test. Figure 1 The in situ infrared ethylbenzene transient reaction characterization results of the catalyst obtained in this example are shown in Figure 3 In the catalyst, the exposed crystal surface area of TiO2 (001) accounts for 93% of the total exposed crystal surface area of TiO2. In the in-situ infrared test, the maximum value of the Kubelka-Munk intensity of the ethylbenzene adsorption vibration peak is 0.85.
[0063] 100 mL of catalyst was loaded into the reactor and the reaction mixture was heated to 40 % under 70 kPa (absolute pressure) and 1.0 h-1 liquid hourly velocity of ethylbenzene. -1 The performance evaluation was carried out under the conditions of reaction temperature 620°C and water ratio 1.0 (wt). The catalyst composition and the evaluation results of the reaction for 100 h are shown in Table 1. The stability evaluation results are shown in Table 2.
[0064] Example 2
[0065] (1) According to the mass ratio of hydrofluoric acid, alkali M, and Ti source of 1:0.95:16.34, tetrabutyl titanate, 40wt% hydrofluoric acid, and tetrapropylammonium hydroxide were weighed and mixed, stirred for 30 minutes, and then placed in an autoclave with a polytetrafluoroethylene liner and kept at 180°C for 24 hours. After the autoclave was naturally cooled (natural cooling rate was 5°C / min), the product was centrifuged, washed with deionized water and anhydrous ethanol, and dried at 80°C for 12 hours. Then it was calcined at 650°C for 2 hours to obtain TiO2 solid.
[0066] (2) In parts by weight, weigh 68 parts of ferric oxide equivalent to Fe2O3, 8.5 parts of potassium carbonate equivalent to K2O, 7.2 parts of cerium nitrate equivalent to CeO2, 5.3 parts of ammonium molybdate equivalent to MoO3, 3.6 parts of manganese nitrate equivalent to MnO2, 1.2 parts of cobalt acetate equivalent to Co3O4 and 6.2 parts of titanium dioxide solid obtained in step (1) equivalent to TiO2, stir in a mixing container for 2 hours until the mixture is uniformly mixed and add an appropriate amount of water. The amount of water added is 21wt% of the total amount of raw materials.
[0067] Then, the pellets were extruded and pelletized to obtain pellets with a diameter of 3 mm and a length of 5 mm, which were placed in an oven and dried at 80°C for 4 hours and 150°C for 10 hours. Then, the pellets were placed in a muffle furnace and calcined at 800°C for 5 hours to obtain a monolithic regular finished catalyst. The heating rate during the calcination process was 10°C / min.
[0068] The exposed crystal surface area of TiO2 (001) in the catalyst accounts for 66% of the total exposed crystal surface area of TiO2. In the in-situ infrared test, the maximum value of the Kubelka-Munk intensity of the ethylbenzene adsorption vibration peak is 0.56.
[0069] 100 mL of catalyst was loaded into the reactor and the reaction mixture was heated to 40 % under 70 kPa (absolute pressure) and 1.0 h-1 liquid hourly velocity of ethylbenzene. -1 The performance evaluation was carried out under the conditions of reaction temperature of 620°C and water ratio of 1.0 (wt %). The catalyst composition and the evaluation results of the reaction for 100 h are shown in Table 1.
[0070] Example 3
[0071] (1) According to the mass ratio of hydrofluoric acid, alkali M, and Ti source of 1:2.79:13.48, tetrabutyl titanate, 40wt% hydrofluoric acid, and tetrapropylammonium hydroxide were weighed and mixed, stirred for 30 minutes, and then placed in an autoclave with a polytetrafluoroethylene liner and kept at 180°C for 24 hours. After the autoclave was naturally cooled (natural cooling rate was 5°C / min), the product was centrifuged, washed with deionized water and anhydrous ethanol, and dried at 80°C for 12 hours. Then it was calcined at 650°C for 2 hours to obtain TiO2 solid.
[0072] (2) In parts by weight, weigh 68 parts of ferric oxide equivalent to Fe2O3, 8.5 parts of potassium carbonate equivalent to K2O, 7.2 parts of cerium nitrate equivalent to CeO2, 5.3 parts of ammonium molybdate equivalent to MoO3, 3.6 parts of manganese nitrate equivalent to MnO2, 1.2 parts of cobalt acetate equivalent to Co3O4 and 6.2 parts of titanium dioxide solid obtained in step (1) equivalent to TiO2, stir in a mixing container for 2 hours until the mixture is uniformly mixed and add an appropriate amount of water. The amount of water added is 21wt% of the total amount of raw materials.
[0073] Then, the pellets were extruded and pelletized to obtain pellets with a diameter of 3 mm and a length of 5 mm, which were placed in an oven and dried at 80°C for 4 hours and 150°C for 10 hours. Then, the pellets were placed in a muffle furnace and calcined at 800°C for 5 hours to obtain a monolithic regular finished catalyst. The heating rate during the calcination process was 10°C / min.
[0074] The exposed crystal surface area of TiO2 (001) in the catalyst accounts for 64% of the total exposed crystal surface area of TiO2. In the in-situ infrared test, the maximum value of the Kubelka-Munk intensity of the ethylbenzene adsorption vibration peak is 0.53.
[0075] 100 mL of catalyst was loaded into the reactor and the reaction mixture was heated to 40 % under 70 kPa (absolute pressure) and 1.0 h-1 liquid hourly velocity of ethylbenzene. -1 The performance evaluation was carried out under the conditions of reaction temperature 620°C and water ratio 1.0 (wt). The catalyst composition and the evaluation results of the reaction for 100 h are shown in Table 1. The stability evaluation results are shown in Table 2.
[0076] Example 4
[0077] (1) According to the mass ratio of hydrofluoric acid, alkali M, and Ti source of 1:2.23:13.48, tetrabutyl titanate, 40wt% hydrofluoric acid, and tetrapropylammonium hydroxide were weighed and mixed, stirred for 30 minutes, and then placed in an autoclave with a polytetrafluoroethylene liner and kept at 180°C for 24 hours. After the autoclave was naturally cooled (natural cooling rate was 5°C / min), the product was centrifuged, washed with deionized water and anhydrous ethanol, and dried at 80°C for 12 hours. Then it was calcined at 650°C for 2 hours to obtain TiO2 solid.
[0078] (2) In parts by weight, weigh 68 parts of ferric oxide equivalent to Fe2O3, 8.5 parts of potassium carbonate equivalent to K2O, 7.2 parts of cerium nitrate equivalent to CeO2, 5.3 parts of ammonium molybdate equivalent to MoO3, 3.6 parts of manganese nitrate equivalent to MnO2, 1.2 parts of cobalt acetate equivalent to Co3O4 and 6.2 parts of titanium dioxide solid obtained in step (1) equivalent to TiO2, stir in a mixing container for 2 hours until the mixture is uniformly mixed and add an appropriate amount of water. The amount of water added is 21wt% of the total amount of raw materials.
[0079] Then, the pellets were extruded and pelletized to obtain pellets with a diameter of 3 mm and a length of 5 mm, which were placed in an oven and dried at 80°C for 4 hours and 150°C for 10 hours. Then, the pellets were placed in a muffle furnace and calcined at 800°C for 5 hours to obtain a monolithic regular finished catalyst. The heating rate during the calcination process was 10°C / min.
[0080] The exposed crystal surface area of TiO2 (001) in the catalyst accounts for 88% of the total exposed crystal surface area of TiO2. In the in-situ infrared test, the maximum value of the Kubelka-Munk intensity of the ethylbenzene adsorption vibration peak is 0.78.
[0081] 100 mL of catalyst was loaded into the reactor and the reaction mixture was heated to 40 % under 70 kPa (absolute pressure) and 1.0 h-1 liquid hourly velocity of ethylbenzene. -1 The performance evaluation was carried out under the conditions of reaction temperature of 620°C and water ratio of 1.0 (wt %). The catalyst composition and the evaluation results of the reaction for 100 h are shown in Table 1.
[0082] Example 5
[0083] (1) According to the mass ratio of hydrofluoric acid, alkali M, and Ti source of 1:0.78:15.36, tetrabutyl titanate, 40wt% hydrofluoric acid, and tetrapropylammonium hydroxide were weighed and mixed, stirred for 30 minutes, and then placed in an autoclave with a polytetrafluoroethylene liner and kept at 180°C for 24 hours. After the autoclave was naturally cooled (natural cooling rate was 5°C / min), the product was centrifuged, washed with deionized water and anhydrous ethanol, and dried at 80°C for 12 hours. Then it was calcined at 650°C for 2 hours to obtain TiO2 solid.
[0084] (2) In parts by weight, weigh 68 parts of ferric oxide equivalent to Fe2O3, 8.5 parts of potassium carbonate equivalent to K2O, 7.2 parts of cerium nitrate equivalent to CeO2, 5.3 parts of ammonium molybdate equivalent to MoO3, 3.6 parts of manganese nitrate equivalent to MnO2, 1.2 parts of cobalt acetate equivalent to Co3O4 and 6.2 parts of titanium dioxide solid obtained in step (1) equivalent to TiO2, stir in a mixing container for 2 hours until the mixture is uniformly mixed and add an appropriate amount of water. The amount of water added is 21wt% of the total amount of raw materials.
[0085] Then, the pellets were extruded and pelletized to obtain pellets with a diameter of 3 mm and a length of 5 mm, which were placed in an oven and dried at 80°C for 4 hours and 150°C for 10 hours. Then, the pellets were placed in a muffle furnace and calcined at 800°C for 5 hours to obtain a monolithic regular finished catalyst. The heating rate during the calcination process was 10°C / min.
[0086] The exposed crystal surface area of TiO2 (001) in the catalyst accounts for 82% of the total exposed crystal surface area of TiO2. In the in-situ infrared test, the maximum value of the Kubelka-Munk intensity of the ethylbenzene adsorption vibration peak is 0.71.
[0087] 100 mL of catalyst was loaded into the reactor and the reaction mixture was heated to 40 % under 70 kPa (absolute pressure) and 1.0 h-1 liquid hourly velocity of ethylbenzene. -1 The performance evaluation was carried out under the conditions of reaction temperature of 620°C and water ratio of 1.0 (wt %). The catalyst composition and the evaluation results of the reaction for 100 h are shown in Table 1.
[0088] Example 6
[0089] (1) According to the mass ratio of hydrofluoric acid, alkali M, and Ti source of 1:1.67:14.55, tetrabutyl titanate, 40wt% hydrofluoric acid, and tetrapropylammonium hydroxide were weighed and mixed, stirred for 30 minutes, and then placed in an autoclave with a polytetrafluoroethylene liner and kept at 180°C for 24 hours. After the autoclave was naturally cooled (natural cooling rate was 5°C / min), the product was centrifuged, washed with deionized water and anhydrous ethanol, and dried at 80°C for 12 hours. Then it was calcined at 650°C for 2 hours to obtain TiO2 solid.
[0090] (2) In parts by weight, weigh 68 parts of ferric oxide equivalent to Fe2O3, 8.5 parts of potassium carbonate equivalent to K2O, 7.2 parts of cerium nitrate equivalent to CeO2, 5.3 parts of ammonium molybdate equivalent to MoO3, 3.6 parts of manganese nitrate equivalent to MnO2, 1.2 parts of cobalt acetate equivalent to Co3O4 and 6.2 parts of titanium dioxide solid obtained in step (1) equivalent to TiO2, stir in a mixing container for 2 hours until the mixture is uniformly mixed and add an appropriate amount of water. The amount of water added is 21wt% of the total amount of raw materials.
[0091] Then, the pellets were extruded and pelletized to obtain pellets with a diameter of 3 mm and a length of 5 mm, which were placed in an oven and dried at 80°C for 4 hours and 150°C for 10 hours. Then, the pellets were placed in a muffle furnace and calcined at 800°C for 5 hours to obtain a monolithic regular finished catalyst. The heating rate during the calcination process was 10°C / min.
[0092] The exposed crystal surface area of TiO2 (001) in the catalyst accounts for 85% of the total exposed crystal surface area of TiO2. In the in-situ infrared test, the maximum value of the Kubelka-Munk intensity of the ethylbenzene adsorption vibration peak is 0.75.
[0093] 100 mL of catalyst was loaded into the reactor and the reaction mixture was heated to 40 % under 70 kPa (absolute pressure) and 1.0 h-1 liquid hourly velocity of ethylbenzene. -1 The performance evaluation was carried out under the conditions of reaction temperature of 620°C and water ratio of 1.0 (wt %). The catalyst composition and the evaluation results of the reaction for 100 h are shown in Table 1.
[0094] Example 7
[0095] (1) According to the mass ratio of hydrofluoric acid, alkali M, and Ti source of 1:0.78:13.48, tetrabutyl titanate, 40wt% hydrofluoric acid, and tetrapropylammonium hydroxide were weighed and mixed, stirred for 30 minutes, and then placed in an autoclave with a polytetrafluoroethylene liner and kept at 180°C for 24 hours. After the autoclave was naturally cooled (natural cooling rate was 5°C / min), the product was centrifuged, washed with deionized water and anhydrous ethanol, and dried at 80°C for 12 hours. Then it was calcined at 650°C for 2 hours to obtain TiO2 solid.
[0096] (2) In parts by weight, weigh 68 parts of Fe2O3 equivalent to ferric oxide, 8.5 parts of K2O equivalent to potassium carbonate, 7.2 parts of CeO2 equivalent to cerium nitrate, 5.8 parts of MoO3 equivalent to ammonium molybdate, 4.6 parts of MnO2 equivalent to manganese nitrate, 1.7 parts of Co3O4 equivalent to cobalt acetate and 4.2 parts of TiO2 equivalent to the titanium dioxide solid obtained in step (1), stir in a mixing container for 2 hours until the mixture is uniformly mixed and add an appropriate amount of water. The amount of water added is 21wt% of the total amount of raw materials.
[0097] Then, the pellets were extruded and pelletized to obtain pellets with a diameter of 3 mm and a length of 5 mm, which were placed in an oven and dried at 80°C for 4 hours and 150°C for 10 hours. Then, the pellets were placed in a muffle furnace and calcined at 800°C for 5 hours to obtain a monolithic regular finished catalyst. The heating rate during the calcination process was 10°C / min.
[0098] The exposed crystal surface area of TiO2 (001) in the catalyst accounts for 77% of the total exposed crystal surface area of TiO2. In the in-situ infrared test, the maximum value of the Kubelka-Munk intensity of the ethylbenzene adsorption vibration peak is 0.68.
[0099] 100 mL of catalyst was loaded into the reactor and the reaction mixture was heated to 40 % under 70 kPa (absolute pressure) and 1.0 h-1 liquid hourly velocity of ethylbenzene. -1The performance evaluation was carried out under the conditions of reaction temperature of 620°C and water ratio of 1.0 (wt %). The catalyst composition and the evaluation results of the reaction for 100 h are shown in Table 1.
[0100] Example 8
[0101] (1) According to the mass ratio of hydrofluoric acid, alkali M, and Ti source of 1:0.78:13.48, tetrabutyl titanate, 40wt% hydrofluoric acid, and tetrapropylammonium hydroxide were weighed and mixed, stirred for 30 minutes, and then placed in an autoclave with a polytetrafluoroethylene liner and kept at 180°C for 24 hours. After the autoclave was naturally cooled (natural cooling rate was 5°C / min), the product was centrifuged, washed with deionized water and anhydrous ethanol, and dried at 80°C for 12 hours. Then it was calcined at 650°C for 2 hours to obtain TiO2 solid.
[0102] (2) In parts by weight, weigh 68 parts of Fe2O3 equivalent to ferric oxide, 8.5 parts of K2O equivalent to potassium carbonate, 6.2 parts of CeO2 equivalent to cerium nitrate, 4.8 parts of MoO3 equivalent to ammonium molybdate, 3.1 parts of MnO2 equivalent to manganese nitrate, 1.2 parts of Co3O4 equivalent to cobalt acetate and 8.2 parts of TiO2 equivalent to the titanium dioxide solid obtained in step (1), stir in a mixing container for 2 hours until the mixture is uniformly mixed and add an appropriate amount of water. The amount of water added is 21wt% of the total amount of raw materials.
[0103] Then, the pellets were extruded and pelletized to obtain pellets with a diameter of 3 mm and a length of 5 mm, which were placed in an oven and dried at 80°C for 4 hours and 150°C for 10 hours. Then, the pellets were placed in a muffle furnace and calcined at 800°C for 5 hours to obtain a monolithic regular finished catalyst. The heating rate during the calcination process was 10°C / min.
[0104] The exposed crystal surface area of TiO2 (001) in the catalyst accounts for 74% of the total exposed crystal surface area of TiO2.
[0105] In the in-situ infrared test, the maximum Kubelka-Munk intensity of the ethylbenzene adsorption vibration peak was 0.64.
[0106] 100 mL of catalyst was loaded into the reactor and the reaction mixture was heated to 40 % under 70 kPa (absolute pressure) and 1.0 h-1 liquid hourly velocity of ethylbenzene. -1 The performance evaluation was carried out under the conditions of reaction temperature 620°C and water ratio 1.0 (wt). The catalyst composition and the evaluation results of the reaction for 100 h are shown in Table 1. The stability evaluation results are shown in Table 2.
[0107] Example 9
[0108] Same as Example 1, except that the catalyst composition is different. The feed amount of step (2) is shown in Table 1. The test results are shown in Table 1.
[0109] The exposed crystal surface area of TiO2 (001) in the catalyst accounts for 93% of the total exposed crystal surface area of TiO2.
[0110] In the in-situ infrared test, the maximum Kubelka-Munk intensity of the ethylbenzene adsorption vibration peak was 0.78.
[0111] Example 10
[0112] Same as Example 1, except that the base M is aqueous ammonia. In step (1), tetrabutyl titanate, 40 wt% hydrofluoric acid and 25 wt% aqueous ammonia are weighed and mixed according to the mass ratio of hydrofluoric acid, base M and Ti source of 1:0.78:13.48.
[0113] The exposed crystal surface area of TiO2 (001) in the catalyst accounts for 89% of the total exposed crystal surface area of TiO2.
[0114] In the in-situ infrared test, the maximum Kubelka-Munk intensity of the ethylbenzene adsorption vibration peak was 0.80.
[0115] Comparative Example 1
[0116] (1) According to the mass ratio of hydrofluoric acid, alkali M, and Ti source of 1:3.35:16.82, tetrabutyl titanate, 40wt% hydrofluoric acid, and tetrapropylammonium hydroxide were weighed and mixed, stirred for 30 minutes, and then placed in an autoclave with a polytetrafluoroethylene liner and kept at 180°C for 24 hours. After the autoclave was naturally cooled (natural cooling rate was 5°C / min), the product was centrifuged, washed with deionized water and anhydrous ethanol, and dried at 80°C for 12 hours. Then it was calcined at 650°C for 2 hours to obtain TiO2 solid.
[0117] (2) In parts by weight, weigh 68 parts of ferric oxide equivalent to Fe2O3, 8.5 parts of potassium carbonate equivalent to K2O, 7.2 parts of cerium nitrate equivalent to CeO2, 5.3 parts of ammonium molybdate equivalent to MoO3, 3.6 parts of manganese nitrate equivalent to MnO2, 1.2 parts of cobalt acetate equivalent to Co3O4 and 6.2 parts of titanium dioxide solid obtained in step (1) equivalent to TiO2, stir in a mixing container for 2 hours until the mixture is uniformly mixed and add an appropriate amount of water. The amount of water added is 21wt% of the total amount of raw materials.
[0118] Then, the pellets were extruded and pelletized to obtain pellets with a diameter of 3 mm and a length of 5 mm, which were placed in an oven and dried at 80°C for 4 hours and 150°C for 10 hours. Then, the pellets were placed in a muffle furnace and calcined at 800°C for 5 hours to obtain a monolithic regular finished catalyst. The heating rate during the calcination process was 10°C / min.
[0119] The main exposed crystal surface photos of the catalyst obtained in this example are shown in HR-TEM test. Figure 2 The in situ infrared ethylbenzene transient reaction characterization results of the catalyst obtained in this example are shown in Figure 4 The exposed crystal surface area of TiO2 (001) in the catalyst accounts for 52% of the total exposed crystal surface area of TiO2.
[0120] In the in-situ infrared test, the maximum Kubelka-Munk intensity of the ethylbenzene adsorption vibration peak was 0.41.
[0121] 100 mL of catalyst was loaded into the reactor and the reaction mixture was heated to 40 % under 70 kPa (absolute pressure) and 1.0 h-1 liquid hourly velocity of ethylbenzene. -1 The performance evaluation was carried out under the conditions of reaction temperature 620°C and water ratio 1.0 (wt). The catalyst composition and the evaluation results of the reaction for 100 h are shown in Table 1. The stability evaluation results are shown in Table 2.
[0122] Comparative Example 2
[0123] (1) According to the mass ratio of hydrofluoric acid, alkali M, and Ti source of 1:1.78:17.25, tetrabutyl titanate, 40wt% hydrofluoric acid, and tetrapropylammonium hydroxide were weighed and mixed, stirred for 30 minutes, and then placed in an autoclave with a polytetrafluoroethylene liner and kept at 180°C for 24 hours. After the autoclave was naturally cooled (natural cooling rate was 5°C / min), the product was centrifuged, washed with deionized water and anhydrous ethanol, and dried at 80°C for 12 hours. Then it was calcined at 650°C for 2 hours to obtain TiO2 solid.
[0124] (2) In parts by weight, weigh 68 parts of ferric oxide equivalent to Fe2O3, 8.5 parts of potassium carbonate equivalent to K2O, 7.2 parts of cerium nitrate equivalent to CeO2, 5.3 parts of ammonium molybdate equivalent to MoO3, 3.6 parts of manganese nitrate equivalent to MnO2, 1.2 parts of cobalt acetate equivalent to Co3O4 and 6.2 parts of titanium dioxide solid obtained in step (1) equivalent to TiO2, stir in a mixing container for 2 hours until the mixture is uniformly mixed and add an appropriate amount of water. The amount of water added is 21wt% of the total amount of raw materials.
[0125] Then, the pellets were extruded and pelletized to obtain pellets with a diameter of 3 mm and a length of 5 mm, which were placed in an oven and dried at 80°C for 4 hours and 150°C for 10 hours. Then, the pellets were placed in a muffle furnace and calcined at 800°C for 5 hours to obtain a monolithic regular finished catalyst. The heating rate during the calcination process was 10°C / min.
[0126] The exposed crystal surface area of TiO2 (001) in the catalyst accounts for 56% of the total exposed crystal surface area of TiO2. In the in-situ infrared test, the maximum value of the Kubelka-Munk intensity of the ethylbenzene adsorption vibration peak is 0.44.
[0127] 100 mL of catalyst was loaded into the reactor and the reaction mixture was heated to 40 % under 70 kPa (absolute pressure) and 1.0 h-1 liquid hourly velocity of ethylbenzene. -1 The performance evaluation was carried out under the conditions of reaction temperature 620°C and water ratio 1.0 (wt). The catalyst composition and the evaluation results of the reaction for 100 h are shown in Table 1. The stability evaluation results are shown in Table 2.
[0128] Comparative Example 3
[0129] (1) Weigh 25 mL of tetrabutyl titanate and place it in an autoclave lined with polytetrafluoroethylene, and keep it at 180°C for 24 hours. After the autoclave is cooled naturally (the natural cooling rate is 5°C / min), the product is dried at 80°C for 12 hours after centrifugation, deionized water and anhydrous ethanol washing. Then, it is calcined at 650°C for 2 hours to obtain TiO2 solid.
[0130] (2) In parts by weight, weigh 68 parts of ferric oxide equivalent to Fe2O3, 8.5 parts of potassium carbonate equivalent to K2O, 7.2 parts of cerium nitrate equivalent to CeO2, 5.3 parts of ammonium molybdate equivalent to MoO3, 3.6 parts of manganese nitrate equivalent to MnO2, 1.2 parts of cobalt acetate equivalent to Co3O4 and 6.2 parts of titanium dioxide solid obtained in step (1) equivalent to TiO2, stir in a mixing container for 2 hours until the mixture is uniformly mixed and add an appropriate amount of water. The amount of water added is 21wt% of the total amount of raw materials.
[0131] Then, the pellets were extruded and pelletized to obtain pellets with a diameter of 3 mm and a length of 5 mm, which were placed in an oven and dried at 80°C for 4 hours and 150°C for 10 hours. Then, the pellets were placed in a muffle furnace and calcined at 800°C for 5 hours to obtain a monolithic regular finished catalyst. The heating rate during the calcination process was 10°C / min.
[0132] The exposed crystal surface area of TiO2 (001) in the catalyst accounts for 39% of the total exposed crystal surface area of TiO2. In the in-situ infrared test, the maximum value of the Kubelka-Munk intensity of the ethylbenzene adsorption vibration peak is 0.30.
[0133] 100 mL of catalyst was loaded into the reactor and the reaction mixture was heated to 40 % under 70 kPa (absolute pressure) and 1.0 h-1 liquid hourly velocity of ethylbenzene. -1 The performance evaluation was carried out under the conditions of reaction temperature 620°C and water ratio 1.0 (wt). The catalyst composition and the evaluation results of the reaction for 100 h are shown in Table 1. The stability evaluation results are shown in Table 2.
[0134] Table 1 Styrene catalyst compositions of the examples and comparative examples and evaluation results of the reaction time of 100 h
[0135]
[0136]
[0137] Table 2 Evaluation results of styrene catalyst stability of examples and comparative examples
[0138]
[0139] The above describes the specific implementation of the present invention in detail, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the various technical features being combined in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A catalyst for preparing styrene by dehydrogenating ethylbenzene, comprising Fe2O3, K2O, CeO2, MoO3, TiO2, MnO2, and Co3O4, wherein: The exposed crystal plane area of TiO2 (001) accounts for more than 60% of the total exposed crystal plane area of TiO2.
2. The catalyst according to claim 1, characterized in that The catalyst, based on the total mass of the catalyst and calculated by mass fraction, includes the following components: (a) 58% to 76% Fe2O3; (b) 6% to 12% K2O; (c) 5% to 10% CeO2; (d) 3% to 7.5% MoO3; (e) 4% to 8.5% TiO2; (f) 1.8% to 5.4% MnO2; (g) 0.6% to 1.8% Co3O4.
3. A method for preparing the catalyst according to claim 1 or 2, comprising: (1) mixing a Ti source, hydrofluoric acid, and a base M uniformly and then performing a first calcination; the base M comprises at least one selected from ammonia water and a quaternary ammonium base; (2) The calcined product of step (1) is uniformly mixed with Fe source, K source, Ce source, Mo source, Mn source and Co source, molded and calcined for the second time to obtain the catalyst.
4. The preparation method according to claim 3, characterized in that: In step (1), the quaternary ammonium base includes at least one selected from tetramethylammonium hydroxide, tetraethylammonium hydroxide, and tetrapropylammonium hydroxide, preferably at least one selected from tetrapropylammonium hydroxide and tetraethylammonium hydroxide; And / or, the Ti source in step (1) includes at least one of tetrabutyl titanate, tetraisopropyl titanate, titanium tetrachloride and titanium sulfate, preferably tetrabutyl titanate and / or tetraisopropyl titanate.
5. The preparation method according to claim 3, characterized in that: In step (1), the mass ratio of the hydrofluoric acid, the base M, and the Ti source is 1:0.17-3.13:12.4-16.
5.
6. The preparation method according to claim 3, characterized in that: In step (1), the mass ratio of the hydrofluoric acid, the base M, and the Ti source is 1:0.45-2.6:13.05-15.
63.
7. The preparation method according to claim 3, characterized in that: The first calcination conditions in step (1) are: calcination temperature is 550-800° C., preferably 600-750° C.; and / or calcination time is 3-5 h, preferably 1.5-3.5 h.
8. The preparation method according to claim 3, characterized in that: In step (2), the conditions for the second calcination are: calcination temperature of 600-900°C; calcination time of 3-7h; heating rate of 10-15°C / min.
9. The preparation method according to claim 3, characterized in that: In step (2), the Fe source, K source, Ce source, Mo source, Mn source, and Co source are oxides and / or salts; Further preferably, the Fe source includes one or more of ferric oxide, ferric chloride, ferric acetate, ferric nitrate, and ferric sulfate; And / or, the K source includes one or more of potassium carbonate, potassium bicarbonate, potassium nitrate, potassium chloride, and potassium sulfate; And / or, the Ce source includes one or more of cerium carbonate, cerium oxalate, cerium nitrate, cerium acetate, cerium chloride, and cerium sulfate; And / or, the Mo source includes one or more of ammonium molybdate and ammonium phosphomolybdate; And / or, the Mn source includes one or more of manganese dioxide, manganese chloride, manganese acetate, manganese nitrate, and manganese sulfate; And / or, the Co source includes one or more of cobalt nitrate, cobalt acetate, cobalt chloride, cobalt sulfate, and cobalt acetylacetonate.
10. Use of the catalyst according to any one of claims 1 to 2 or the catalyst prepared by the preparation method according to any one of claims 3 to 9 in the reaction of dehydrogenating ethylbenzene to produce styrene.
Citation Information
Patent Citations
Diethylbenzene dehydrogenation catalyst and preparation method thereof
CN107790149A
Catalyst for oxidative dehydrogenation of butene as well as preparation method and application thereof
CN114073959A
Ethylbenzene dehydrogenation catalyst as well as preparation method and application thereof
CN115957773A
Catalyst for preparing styrene through ethylbenzene dehydrogenation as well as preparation method and application of catalyst
CN115957775A
Catalyst for dehydrogenation of alkyl aromatic hydrocarbon and preparation method therefor
WO2020078303A1